Syncytial nuclei accumulate at the villous surface in IUGR while proliferation is unchanged. (December 2017) - Haeussner, E.; Schmitz, C.; Grynspan, D.; Edler von Koch, F.; Frank, H.-G.
Abstract: Introduction: Placental syncytiotrophoblast is responsible for feto-maternal nutrient exchange during pregnancy. It is assumed that in IUGR, placental dysfunction is crucially bound to compromised stability and function of syncytiotrophoblast, the latter being related to altered proliferation of villous trophoblast. Cell cycle data obtained on conventional thin sections has produced inconsistent results. In the present study we investigated cell cycle markers found in the villous trophoblast using a novel 3D histological quantification method. Methods and findings: We analyzed 40 placentas from IUGR pregnancies and 42 placentas from clinically normal pregnancies by immunohistochemical detection of the cell cycle marker PCNA. Nuclei immuno-positive for PCNA were quantified using 3D microscopy, and the results were compared to corresponding results obtained on conventional thin histological sections. These data did not show any evidence of altered trophoblast proliferation in IUGR, while the density of post-proliferative (i.e. PCNA-negative) trophoblast nuclei was statistically significantly increased in IUGR. The latter could be revealed by 3D topological microscopy, but not by conventional histology of thin sections. Discussion: The data of the present study indicate a previously unknown type of regulation of syncytial stability and function, independent of proliferation. We hypothesize that in IUGR, post-proliferative trophoblast nuclei accumulate at the villous surface of peripheral villous branches. This could possibly reflect the presence of an unknown mechanism controlling syncytial function and stability by modulation of syncytial passage time rather than by modulation of proliferative supply. Highlights: 3D mapping of proliferative and non-proliferative trophoblast nuclei. 3D microscopy avoids the reference trap of section-based index counting. Density of proliferative nuclei is unaltered in IUGR in 2D and 3D microscopy. The density of non-proliferative nuclei is increased in IUGR in 3D microscopy.